PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GI (GROUP INVESTIGATION) TERHADAP KETERAMPILAN GENERIK SAINS SISWA - Sari’ah Sari’ah; Saiful Prayogi; Sukainil Ahzan (Lensa: Jurnal Kependidikan Fisika, 2015)
The purpose of this study was to determine the effect of cooperative learning model of group investigation type against scince generic skills of students. This research was a quasi-experimental. The population in the study was a grade VIII MTS Nurul Falah NW Lajut with 36 students. Sampling was derived by random sampling where the 16 students of VIII A as on experimental class and VIII B as a control class with 20 students.Based on pretest data analysis, obtained an average value of 31,25 experimental class and control class was 42,2.Posttest analysis showed an average grade of 65,75 experimental and control class was 61,6.  The data analysis technique was t-test. It show t- test= 5,80 and t-table = 1,67. Because of  t-count is greater than the  t- table, it can be concluded that there were the effect of cooperative learning model of group investigation generic against science skills of student.